Impact of Generative Artificial Intelligence on the Work of Digital Marketing Professionals - Martins, M.; Alturas, B.; Lapa, T. (Proceedings of ICMarkTech 2025, 2026)
Within the framework of Industry 5.0—where humans and machines work together to achieve business objectives—this study investigates the influence of generative Artificial Intelligence (AI) on the everyday activities of digital marketing professionals in Portugal, particularly in the financial and retail sectors. Through semi-structured interviews, the research reveals that although the use of generative AI is still in its early phases, there is a noticeable trend toward exploring its capabilities, especially in content production. Most professionals are already applying generative AI in different tasks, acknowledging its advantages in terms of time efficiency and enhanced work quality. However, the study also uncovered several obstacles to fully integrating generative AI into company processes, such as data privacy concerns in the financial industry, along with the absence of well-defined strategies and certain technological constraints in both sectors. The findings emphasise the importance for Portuguese companies to establish clear approaches for the effective adoption of generative AI in digital marketing. In general, businesses in both sectors are still in the experimental phase of incorporating this technology into their routine marketing activities.